Eksistensi Penerimaan (Qabul) Dalam Akad Wakaf - Suchamdi Suchamdi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
This paper is to describe core problem of acceptance (qabul) of wakaf transaction which Islamic law schools compare. There are several analysis statements releted to acceptance (qabul) of wakaf. At least, there are two mainstreams statements which each of them points out, one says that prerequisites are important and one states vice versa. In its own Islamic schools, there are, even, different theses. A lot of spcialists seem to accept school which considers acceptance as prerequites of wakaf. Acceptance of wakaf substantially classifies that properties donated for religious (wakaf) or community use and donator declared officially will not be taken off for good. It goes with wakaf regulation (law) in Indonesia which states that wakaf properties cannot be cancel out.